High impact IELTS : - Bourne, Patrick (Pearson New Zealand, 2004)
High impact IELTS is a comprehensive book aimed at helping students pass the academic module of the IELTS exam. From an overall guide to the IELTS exam right up to suggestions for preparation the night before, Hight impact IELTS covers all the details essential for a good result.